IMAGE DETECTION IN THE AIMBOT PROGRAM USING YOLOV4-TINY - Arief Kelik Nugroho; Ipung Permadi; Ahmad Habiballah (Jurnal Teknik Informatika (Jutif), 2023)
Cheats are a way for players to gain an unfair advantage. The rise of cheats in online games encourages game producers to increase the security of their games by implementing an anti-cheat system. However, the currently widely circulated anti-cheat system only monitors incoming and outgoing raw data. With the widespread use of image detection systems, we can fool most of today's anti-cheat systems. This can be done by capturing the image that appears on the screen and then processing it through the image detection system. From the process, it can be seen whether there are opponents that appear on the screen. If there is, the program will move the mouse to the place where the enemy is and shoot it. This program is built on the core of the YOLOv4-tiny image detection system.